Development of UNO Card Learning Media Economic Growth and Development Material - Aulia Sapitri; Mahmudah Hasanah; Sharfina Amima; Baseran Nor (Journal of Educational Management Research, 2026)
This study aims to develop UNO card-based learning media and analyze its validity and practicality in teaching economic growth and development. In the context of rapid digitalization, learning environments face challenges such as decreased student concentration and over-reliance on technology, which often reduce engagement and learning effectiveness. Therefore, innovative, non-digital, and interactive learning media are needed to support meaningful learning experiences. This research employed a Research and Development (R&D) design using the 4D model, consisting of define, design, develop, and disseminate stages. Data were collected through expert validation sheets, student questionnaires, interviews, and documentation, and analyzed using descriptive quantitative techniques. The findings indicate that the developed media achieved a very high level of validity (96.75%) and practicality (94.4%). The media aligns well with curriculum standards and student characteristics, enhancing its instructional relevance. The interactive game structure increases student motivation, participation, and engagement. The visual and structural design supports readability and usability. The media is flexible and does not require internet access, making it suitable for diverse contexts. It also promotes collaborative and active learning. This study contributes to the development of game-based learning in economics education and recommends further research to examine its effectiveness on learning outcomes.